The genome sequence of the striped dolphin, Stenella coeruleoalba (Meyen, 1833) [version 1; peer review: 2 approved] - Nicholas J. Davison; Phillip A. Morin (Wellcome Open Research)
We present a genome assembly from an individual male Stenella coeruleoalba (the striped dolphin; Chordata; Mammalia; Artiodactyla; Delphinidae). The genome sequence has a total length of 2,691.40 megabases. Most of the assembly is scaffolded into 23 chromosomal pseudomolecules, including the X and Y sex chromosomes. The mitochondrial genome has also been assembled and is 16.39 kilobases in length.